Ice wedge dynamics and local crushing - McKenna, R. F.; Spencer, D. (1993)
A method for analysing the dynamic failure of ice wedges against ships and sloping structures has been developed. The approach is based on beam theory and incorporates local crushing and shear at the contact, as well as flexural failure. Both upward and downward breaking mechanisms are included, and the approach has been useful for assessing ice loads on conical structures. Examples are included to illustrate the influence of in-plane forces on failure loads and the dynamic effect during high speed loading. Peer reviewed: Yes NRC publication: Yes